PENGARUH PERENCANAAN LOGISTIK UMUM TERHADAP PELAYANAN KESEHATAN DI RUMAH SAKIT DR BRATANATA JAMBI - Rahmawati, Resti Dewi; Asyura, Marelda; Febriyahani, Nasywa; Lidhiana Qoriah, Shafa; Diaz Arya, M. Erin (LPPM Universitas Awal Bros, 2025)
According to Sabarguna (2008:91) a hospital is a professional health care institution whose services are provided by doctors, nurses and other health experts. Logistics as a supporting completeness that complements and perfects in providing medical services in hospitals, especially in the aspects of administrative and operational services related to the interests of patients and the interests of hospital employees in carrying out their activities. However, in reality, there are still many hospitals that do not pay serious attention to optimal non-medical logistics management. It can be seen that there are still frequent stock outs and excess stock in the warehouse which can be an obstacle to the smooth provision of health and administrative services and can be a factor that is detrimental to the hospital. Keywords :Non-Medical Logistics Planning At Hospital